The Effect of Capital Structure and Profitability on Company Value in Pharmaceutical Sub-Sector Manufacturing Companies Listed in the Indonesia Stock Exchange - Hayah Masrurah Nurfan; Abdul Rahman Mus; Junaiddin Zakaria (Newinera Publisher, 2024)
The Impact of Capital Structure and Profitability on Company Value in Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Indonesian Stock Exchange. (Supervised by H. Abdul Rahman Mus and Junaiddin Zakaria). This study aimed to rigorously examine the effect of capital structure and profitability on company value in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange.This study employed a quantitative approach using secondary data. This study was conducted on representatives of the Indonesian Stock Exchange in the Indonesian Stock Exchange Gallery located at the Faculty of Economics and Business, Universitas Muslim Indonesia, JL Urip Sumoharjo KM. 5 Makassar, South Sulawesi. The study was carried out from November to December 2023, for around two months. The population in this study were pharmaceutical sub-sector companies listed on the Indonesian Stock Exchange in 2019-2022, for a total of 11 companies. Applying a purposive sampling technique, a number of predetermined criteria resulted in eight pharmaceutical sub-sector companies as samples. The data were analyzed using the Statistical Program for Social Science (SPSS) with multiple linear analysis techniques and classical assumption tests. The results of this study reported that: (1) capital structure demonstrated a positive and significant effect on company value; (2) profitability illustrated a positive and insignificant effect on company value.